PENGARUH KESADARAN WAJIB PAJAK, KUALITAS PELAYANAN, SERTA PERSEPSI TENTANG DENDA PADA KEPATUHAN WAJIB PAJAK REKLAME DI DINAS PENDAPATAN KOTA SURABAYA - PERMANA PUTRA, ANDRY (Jurnal Akuntansi AKUNESA, 2018)
This study aims to determine the effect of taxpayer awareness, service quality, and perceptions of fines on taxpayer compliance compliance in the city income service surabaya. This research uses quantitative approach by using primary data. The sample consisted of 150 samples. Variables used in this study is taxpayer compliance is as a dependent variable whereas taxpayer awareness, service quality, serpa perception of fines as independent. Analytical technique used is multiple linear regression analysis used to measure how big influence between independent variable with dependent variable. The results showed the independent variable awareness of taxpayers, service quality, serpa perception of fines affect taxpayer compliance.